ASOSIASI CENDAWAN MIKORIZA ARBUSKULA (CMA) PADA TEGAKAN AKASIA (Acacia crassicarpa A. Cunn.Ex Benth) DI LAHAN GAMBUT PT. KALIMANTAN SUBUR PERMAI KABUPATEN KUBU RAYA KALIMANTAN BARAT - Yama, Decki; Muin, Abdurrani; Wulandari, Reine Suci (JURNAL HUTAN LESTARI, 2014)
Forest plantation development especially industrial forest plantations (IPF) is an important activity in the critical land use. One of the plants is Acacia crassicarpa. Purpose of this research is to determine the VAM (vesicular arbuscular mycorrhizae) plant associations in A. crassicarpa. in the peatland area of PT. Kalimantan Subur Permai. This research method is the isolation of spores through the examination process gradually wet, coloring the roots, characteristics of spores at the genus level and calculate the percentage of root infection. The results showed that 6 types of spores was found that 5 of the genus Glomus and 1 of the genus Gigaspora and the average percentage of root infection was 22% - 38%. Keywords: Association, vesicular arbuscular mycorrhizae, A. crassicarpa, peatlands.